The Relationship Between Serum Level of Thyroid Hormones and Antioxidant Enzymes in Clinically Healthy Ostriches - Khoshvaghti , Ameneh; Nazifi, Saeed; Mirabad, Mohammad Mehdi; Akbarpour, Bijan (International Journal of Poultry Science, 2012)
Thyroid hormones might be able to regulate the activities of Superoxide Dismutase (SOD), catalase and Glutathione Peroxidase (GPX). The role of thyroid hormones in metabolic pathways and antioxidant enzyme activities are well known in many species. Nevertheless, there is no report describing probable relationship between thyroid hormones status and erythrocyte antioxidant enzymes. This study was undertaken to investigate the relationship between these parameters in ostriches. Blood samples were taken from the jugular vein of 50 clinically healthy ostriches under aseptic conditions during 6 consecutive days of summer. The serum was analyzed for serum profile of thyroid hormones, SOD and GPX activity. There were no significant differences in serum thyroid hormones and antioxidant enzymes in different days (p>0.05). There were significant correlations between SOD and T3 (p = 0.021, r = 0.421), also between f T3 and T4 (p = 0.000, r = 0.997). There was no significant correlation between other parameters.